Semantic-cognitive analysis of the polysemy of the appreciative-augmentative morpheme -azo in Spanish - Villegas Paz, Magali Cleofé (2022)
In this study approaches the phenomenon of polysemy in the appreciative morpheme -azo in Spanish from a semantic-cognitive perspective. The main objective is to explain the way in which the multiple meanings detectable in the uses of lexical forms derived through this suffix are organized. We reconognize that this morphological unit presents a set of motivated categories that form a polysemous network organized by means of a central semantic point or cognitive reference point whose nature is defined by the experience of physical reality, which metaphorically orients the other possible meanings of the radial network. These findings reveal that the possible senses are the product of the determination of a prototypical category linked to size, which extends the network through a mechanism of metaphorical conceptualization.